Potret Literasi Digital Mahasiswa dalam Pembelajaran Sastra - Sembiring, Sri Ulina Br; Lande, Tri; Erawati, Yolani (Jurnal Pendidikan Bahasa dan Sastra Indonesia Metalingua, 2026)
This study aims to describe the level of digital literacy among students in literary studies in the technological era. The method used is descriptive qualitative with 145 students of Indonesian Language and Literature Education Programme at Universitas Negeri Medan as subjects. Data were obtained through questionnaires and analysed descriptively. The results of the study show that the aspects of access and utilisation of digital technology obtained an average score of 3.87, the ability to search for and evaluate digital literary information 3.47, creativity in the production of digital literary content 3.56, and critical attitude and digital ethics 3.73, all of which are in the high category. Meanwhile, the aspect of collaboration in the digital space scored 3.39 (medium category). Overall, the students' digital literacy level was in the high category with an average score of 3.60. These findings indicate that students have been able to access, utilise, and behave ethically in the digital space, but still need to improve in collaboration. A learning strategy is needed to foster cooperation and critical digital literacy through creative projects and a practice-based digital curriculum so that students can become critical, creative, ethical, and collaborative users and creators of digital literature.